Green Construction Principles in the Design of Reinforced Concrete Floor Slabs and Beams as a Sustainability Management Framework - Rahayu Mardikaningsih; Maulana Syahid (Politeknik Kampar, 2026)
The construction sector stands as one of the most resource-intensive human activities, with reinforced concrete accounting for a disproportionately large share of material consumption and carbon emissions in built environments worldwide. This paper examines how sustainability management principles grounded in green construction can be normatively embedded in the design and assessment of reinforced concrete floor slabs and beams. Drawing on a qualitative review of academic and technical literature, the study investigates the structural, material, and managerial dimensions through which green construction principles can be operationalized in the engineering practice of reinforced concrete design. Key areas addressed include material efficiency in slab and beam sizing, the use of supplementary cementitious materials, life cycle perspective in structural decision-making, reinforcement optimization, and the coordination between structural design and construction management. The study affirms that structural reliability and environmental responsibility are not competing objectives, but can be achieved simultaneously through informed, systematic, and principled design decisions.